The Particularity of Perception as an Argument for a Relational View of Experience - Grönroos, Tapio (My University, 2025)
This thesis concerns the nature of perceptual experience. It asks what view of perceptual experience best accommodates the thought that the objects of perceptual experience are the particular objects present in one’s surroundings. Two kinds of theories are considered. On one side of the issue are theories that take perception to be fundamentally representational in nature. According to these theories, perception always involves the instantiation of contentful internal states. The discussion of representational theories focuses on the views of Tyler Burge and Susanna Schellenberg, both of whom explain perceptual particularity in terms of representational content. On the other side of the issue are theories that understand perceptual experience in fundamentally relational terms. Broadly speaking, relational theories have it that, rather than requiring the instantiation of a contentful internal state, perceptual experience is a matter of standing in a relation to the particular entities perceived. Perceptual particularity is thus explained as the obtaining of a relation between the perceiver and the particular perceived. The thesis argues against the thought that contentful internal states mediate perception of particular objects. The argument takes inspiration from John Campbell’s thought that perceptual experience has a specific role to play in explaining the possibility of demonstrative reference and thought about particulars. It is argued that, by appearing as fundamental common factors between veridical and delusive experiences, contentful internal states get in the way of understanding perceptual experience as having this explanatory role and genuinely informing one of the particulars in one’s surroundings. By dispensing with contentful internal states and viewing experience in terms of presentation rather than representation, a relational view of experience can better accommodate the thought that the objects of perceptual experience are the particular objects in one’s surrounding environment.
Keywords: perception, perceptual experience, illusion, hallucination, representational content, representationalism, relationalism, disjunctivism